Financial Sector Assessment Program Update : Republic of Poland - Credit, Growth, and Financial Stability - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
Two main issues at the interface between economic growth and financial stability are germane to this year's article four consultation and the Financial Sector Assessment Program (FSAP) update: the first is why the recent pace of financial catching-up has been so much slower in Poland than in its regional peers, and whether this might hamper Poland's long-term economic prospects; and the second question is how significant the prudential risks associated with rapid growth in housing loans are. The chapter is organized as follows: section II.B discusses credit developments in the last decade and factors driving these developments and assesses implications for economic growth. Section II.C examines reasons for rapid growth of foreign currency lending and implications for financial stability. Section II.D (and appendix) review cross-country experiences with policy responses to rapid credit growth of foreign currency credit and discuss recent policy measures taken in Poland. Section II.E concludes the chapter.